Improved synthesis of some hydroxycoumarins - (:unkn) unknown (Elsevier BV, 1996)
An improved synthesis of some 7-hydroxycoumarin derivatives is reported. Hydroxybenzenes reacted with ß-ketoesters or d,1-matic acid in HClO4 to give good yields of 7-hydroxycoumarins. IR and 1H NMR data for the products are also reported.